Pengaruh Predatory Pricing, Sikap Konsumen dan Pemasaran Interaktif terhadap Peningkatan Penjualan UMKM di TikTok Shop (Studi kasus UMKM kuliner di Jakarta Selatan) - Trian Desa Putra, Trian; Setiawan, Yuli (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2024)
This study aims to examine the impact of predatory pricing, consumer attitudes, and interactive marketing on the increase in sales of SMEs on TikTok Shop, both simultaneously and partially. The research design uses a quantitative method with non-probability sampling techniques. The population of this study consists of culinary SMEs in South Jakarta using TikTok Shop, with a sample size of 100 respondents determined using the Roscoe formula. Data analysis methods include multiple linear regression analysis, uji auto korelasi, F-test (simultaneous), t-test (partial), and Coefficient of Determination (Adjusted R Square) using SPSS 25 software. The results indicate a simultaneous significant effect of the variables Predatory Pricing, Consumer Attitudes, and Interactive Marketing on Sales Improvement. Partially, Predatory Pricing and Consumer Attitudes significantly affect Sales Improvement, while Interactive Marketing does not substantially impact Sales Improvement Keywords: Predatory Pricing, Customer Attitudes, Interactive Marketing, Sales Improvement